Mothers and Fathers Resourcing Early Learning and Development. Issue 4 (December 2014) - Nichols, Sue
YOUNG CHILDREN IN THE preschool period are being positioned as early learners with parents being attributed with responsibility for facilitating their children's learning and development. This study concerns parents' awareness of and access to a broad range of resources which they understood as relevant to this task. Interviews with 25 mothers and eight fathers of children aged birth–six formed the basis of this analysis. Commonalities and differences between mothers and fathers were found which suggest a need for further research into gender as a dimension of parental resourcing. Three themes are explored in the discussion: maternity as an entry point into resource networks; female kin as resource providers; and the internet as a gender equaliser in resource access.